2014
DOI: 10.1186/s40634-014-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction molecular diagnostic technology for monitoring chronic osteomyelitis

Abstract: BackgroundOsteomyelitis is a devastating condition whose treatment relies on the detection of bacteria. The current standard of microbiology culture may not be adequate. Molecular biology based diagnostic procedures for detecting bacteria in orthopaedic infections was previously established, but has not been applied to the setting of chronic osteomyelitis. We aim to determine the applicability of molecular diagnostic procedures for monitoring chronic osteomyelitis, and to evaluate if these procedures are super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…One method used in the past to determine the number of viable microbial cells in culture was based on quantitation of ATP, but with inconsistent results. Our lab actually pioneered the 16S RNA-based RT-PCR method for detecting joint infection [54] and recently adopted it for osteomyelitis [55]. However, this method detects all bacteria, including non-viable bacteria, potentially giving false positives.…”
Section: Discussionmentioning
confidence: 99%
“…One method used in the past to determine the number of viable microbial cells in culture was based on quantitation of ATP, but with inconsistent results. Our lab actually pioneered the 16S RNA-based RT-PCR method for detecting joint infection [54] and recently adopted it for osteomyelitis [55]. However, this method detects all bacteria, including non-viable bacteria, potentially giving false positives.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Radiography showed that by day 28, 100% of the animals in the experimental group suffered bone infection as defined by increased radiolucency around the implant, which is a hallmark of PJI. 40 - 42 Histological analysis of explanted bone from the inoculated group revealed fibrous tissue formation within the bone tunnel that stained positively on Gram’s stain in serial sections, whereas healthy bone formation was observed in the aseptic screw group. 32 The positive Gram’s stain was coincident with particles characteristic of bacteria in size.…”
Section: Discussionmentioning
confidence: 99%
“…1. Ethidium bromide (EtBr) can be used for the staining of amplified DNA product [31,32]. It has UV absorbance maxima at 300 and 360 nm, and an emission maximum at 590 nm, and being a DNA intercalator, EtBr inserts itself between the base pairs in the double helix.…”
Section: Validating Pcrmentioning
confidence: 99%